Adolescent depression: Progress and future challenges in prevention-control activities - (:unkn) unknown (My University, 2004)
It is accepted that depression during adolescence is a highly prevalent yet mostly an under recognized mental health problem. Studies carried out in diverse cultures report prevalence rates ranging from 1% to 50% for adolescent depression. Presence of depression during adolescence, effects the development negatively and creates a tendency towards high-risk behaviors as alcohol, tobacco use and substance abuse. Current research points out that although there is a biological tendency for the development of adolescent depression, psychological and social factors also play an important role. Therefore intervention programs, focusing on particularly psychosocial factors, gain attention for the prevention and control of adolescent depression. The findings from school based studies which aim to prevent adolescent depression through utilizing cognitive behavioral techniques are promising. This paper discusses the burden and the factors influencing the development of depression during adolescence, as well as the objectives, methods, findings and the effectiveness of prevention programs which focus on psychosocial factors.